Technological advancements in transportation and logistics: Exploring circular economy principles through bibliometric insights - Nwaichi, Peter Ikechukwu; Norida, Ridzuan; Nwaichi, Eucharia Oluchi; Umunnawuike, Chika; Nyah, Francis; Abutu, David; Money, Barima; Agi, Augustine Aja (Springer Nature, 2025)
Transportation and logistics sectors face increasing challenges due to resource depletion, population growth, and socio-environmental crises, requiring sustainable solutions. Circular economy (CE) principles offer a framework for enhancing resource efficiency and reducing waste. This study employs a systematic literature review and bibliometric analysis to explore CE-related challenges in transportation and logistics. A total of 350 scholarly articles (2000 – February 2025) from the Scopus® database were analyzed using citation, co-citation, and keyword co-occurrence analyses. Findings reveal a significant rise in research over the past 24 years, with a surge from 2017 to 2024. China, the United States, Saudi Arabia, the United Kingdom, and India emerged as leading contributors to scientific literature in this domain. Key technologies, including the internet of things (IoT), physical internet (PI), cyber-physical systems (CPS), cloud-fog-edge computing, quantum computing, artificial intelligence (AI), blockchain, and big data, are identified as transformative drivers in the sector. The study highlights emerging research areas and unresolved challenges, providing a foundation for further exploration. By integrating CE principles with digital technology, transportation and logistics industry can enhance sustainability, operational efficiency, and resource optimization. This study advances knowledge by mapping research trends and identifying promising technological pathways, aiding policymakers, researchers, and industry professionals in decision-making.